Karma and qada' and qadar : a comparative study - Idahwati @ Irdina Nur'aidah binti Idris (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2007)
The concept of Karma in Buddhism and al-Qada and al-Qadar in Islam are all centred on man's will, action and freedom. Buddhism and Islam both advocate man's freedom and reject the idea of fatalism and determinism. The Buddhists believe in Karma whereas Muslims believe in al-Qada and al-Qadar. The phenomena seem similar but the interpretations differ. This study attempts to make a comparative evaluation between Karma in Buddhism and al-Qada and al-Qadar in Islam. This can help Muslims understand Buddhism and assist the Muslims in the engineering of a better social rapport between these two religious communities. From the study, several findings may be drawn; both religions affirm that man is granted with free will, the concept of Karma in Buddhism and al-Qada and al-Qadar in Islam provokes human being to strive harder in order to be better human beings and responsible for their deeds, and both religions agree that human's action is based on intention which occurs through three ways; mental, verbal and physical. In terms of differences, the concept of Karma strongly rejects the intervention of god because the Buddhists believe that everything in this world is governed by the law of Karma. In Islam, on the other hand, the concept of al-Qada and al-Qadar is related to Allah's Divine Will. All events in life which include life span, provision, time and place of birth and death, and all actions exist within the scope of the Divine Will. Therefore, the Buddhists believe that Karma is the cause of human existence in this world. On the other hand, Islam regards human beings as the creations of Allah, the Almighty, and the main purpose of their existence is only to serve Allah and obey His commands. Thus, human beings are regarded as vicegerents of Allah and they are to carry out a serious amanah (trust) of Allah.